Three-dimensional study of 31 cases of synostotic anterior plagiocephaly before and after surgical management the Lille protocol. Issue 6 (June 2018) - Simon, Ambre; Bocquet, Emmanuelle; Pellerin, Philippe; Vinchon, Matthieu; Dhellemmes, Patrick; Martinot, Véronique; Wolber, Alexis; Calibre, Clotilde; Charlier, Philippe; Guerreschi, Pierre
Abstract: Synostotic anterior plagiocephaly is a rare pathological cranial malformation. Therapeutic options are rarely studied due to the rarity of the malformation and difficulties in diagnosis and care management. The objective of this study was to analyze the results obtained with the Lille protocol based on 62 CT-scans done before and after surgery in 31 patients. A specific analysis was designed for this work. Nine cephalometric measures enabled to evidence on each CT-Scan the corrections made on the fronto-orbital bandeau and the potential impact of surgery on the craniofacial structures. Results show that surgical symmetry of the fronto-orbital bandeau in the transversal plane, according to the symmetrical axis of the semicircular canals, allows a normalization of the skull's growth and morphogenesis for the surgically affected structures but also adjacent ones.